IoT as a service : third International Conference, IoTaaS 2017, Taichung, Taiwan, September 20-22, 2017, Proceedings /: third International Conference, IoTaaS 2017, Taichung, Taiwan, September 20-22, 2017, Proceedings. (2018) - Unknown
No abstract available